Rancang Bangun Aplikasi Android untuk Deteksi Dini Kanker Melanoma - M. Syafiul Umam; Komang Candra Brata; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Melanoma cancer is a type of deadly skin disease. Melanoma cancer caused by the melanocyte cells that produce melanin undergo mutations which makes these cells to grow abnormally and become cancerous. In Indonesia, the total of Melanoma cancer patient has reached 1,609 people and 699 people have died in 2020, while public awareness in Indonesia is still very low. There are several ways to detect melanoma cancer early, one of them are by using the ABCDE method, but not everyone knows about this method. The author wants to make an application for the early detection of melanoma cancer that utilizes images using the CNN algorithm and also provides education about the dangers of melanoma in the hope that users will go to a dermatologist to find irregularities in their skin. The author will develop the application based on needs and implemented using the Java programming language. For application testing there are validation, usability and accuracy tests. For validation testing using the blackbox method with 100% valid results, usability testing using SUS (System Usability Testing) with a score of 73 which is included in the good category, and accuracy testing with a score of 72%.